REGISTROS DE ENFERMAGEM SOBRE LESÃO POR PRESSÃO EM UMA UNIDADE DE TERAPIA INTENSIVA. - D'Albuquerque Almeida, Gabriella Haíssa; de Oliveira Dantas, Gleydson Henrique; Bernardo Nóbrega, Luciana Maria; Palmeira de Morais, Jéssica Lorena; Marques Andrade de Souza, Ana Paula; da Costa Santos, Iolanda Beserra; Buriti Vasconcelos, Josilene de Melo (Enfermagem Atual in Derme)
Objective: to analyze the nursing records, relevant to the occurrence, prevention and treatment of pressure injuries, in the medical records of patients in an Intensive Care Unit. Method: documental, retrospective study, with a quantitative approach, carried out in a teaching hospital, in the Brazilian Northeast. The sample consisted of 46 medical records. Data collection took place in January 2020, obtaining information from nursing forms and recording them in a form developed for the study. The analysis was performed using descriptive statistics, using the Statistical Package for the Social Sciences program, version 24. Results: the prevalence of pressure injuries was 31.82% and the incidence was 11.36%. On patient admission, risk assessment for development of pressure injury was not performed (100%); and in the evaluation of the skin, moisture (6.82%) was the least evaluated parameter, in addition to there being no record of evaluation of turgor. Emphasis was placed on the recording of actions for skin hydration and protection of bony prominences in all patients with and without pressure injuries; and the record of change of position was higher among patients without pressure injuries (29.54%). Among the treatment measures, there was a record of care for the injury in 57.14% of the medical records. Conclusion: the results may suggest questions about failures in carrying out important actions in the care context and/or in their records.